2007
DOI: 10.1007/s10531-007-9214-2
|View full text |Cite
|
Sign up to set email alerts
|

Linking bioprospecting with sustainable development and conservation: the Panama case

Abstract: The limited international resources for economic aid and conservation can only mitigate poverty and losses of biodiversity. Hence, developing nations must establish the capacity to resolve their problems. Additionally, policy-makers and donors need to obtain scientific input on issues such as global change and ecosystem services. We propose that for nations rich in biodiversity, ecosystem services derived from bioprospecting, or drug discovery, could contribute to economic development. In the case where unstud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Harvey (2008) reported that 225 drugs from natural sources were in developmental stages and, of these, 24 had been extracted from animals. The search for medicines and genes from nature has been promoted as a non-destructive use of habitat that promotes human health as well as supporting economic development and conservation (Kursar et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Harvey (2008) reported that 225 drugs from natural sources were in developmental stages and, of these, 24 had been extracted from animals. The search for medicines and genes from nature has been promoted as a non-destructive use of habitat that promotes human health as well as supporting economic development and conservation (Kursar et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…There is a need to promote conservation and to protect species utilized for medicinal purposes considering all the potential of these species, because bioprospecting is one of the incentives for the conservation of species (Kursar et al, 2007). This situation demonstrates the importance of developing more detailed studies focusing on the interactions between humans and reptiles in order to be able to evaluate the true implications of the use of these animals for medicinal purposes and to develop viable strategies for their conservation (Ferreira et al, 2009c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This program conducts most of the studies in Panamanian laboratories, thus providing jobs and boosting the local research skills of students by offering training and practical research experience. This initiative has been constructive in the fields of conservation and sustainable development (Kursar et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Because the research in bioprospecting and related activities and benefits depend on maintaining an intact ecosystem, this activity is recognized as a ecosystem service (Kursar et al 2007). Bioprospecting improves human wellbeing and highlights the value of biodiversity, as emphasized by the Millennium Ecosystem Assessment (2005).…”
Section: Discussionmentioning
confidence: 99%